Propagación vegetativa por injerto tipo momia (púa lateral modificado) en tres clones de cacao de origen ecuatoriano, en el Huallaga Central - Región San Martín - Tulliano Palacios, Gianfranco (2010)
Under a complete Block Design Randomized, with three treatments and four repetitions, investigated the "vegetative propagation by Grafting Type Mummy (Plectrum Lateral Amended) in Three Clones of Cocoa Ecuadorian Origin, in the Central Huallaga - Region San Martin". The plot with a geographical location of a south latitude of 07º10'48'', west longitude 76 45'14'' and to an altitude of 298 m.s.n.m.m., with a Location Policy in the Region San Martin, Province of Huallaga, District of Sacanche in the Sector Huairanga, with the following conditions soil and climate; average temperature of 27 degrees centigrade, and a rainfall of 1200 – 1400 mm/year, with a soil texture clayey., The type of graft was evaluated plectrum lateral amended (type Mummy), using genetic materials introduced origins ecuadorians corresponding to the clones EET – 575 (T3), EET – 576 (T2) and CCN – 51 (T1) witness. The thesis was to determine the percentage of apprehension, diameter of the outbreak of the graft, height of the outbreak of the graft, number of leaves of the outbreak of the graft, and the leaf area of the outbreak of the graft. Concluding that the clones that obtained greater response to the graft plectrum lateral amended type Mummy were the (T3) EET – 575 and (T1) CCN – 51 witness. The (T3) EET – 575, won the largest results in the parameters of a percentage of apprehension with a (100?, diameter of the outbreak of the graft (0.92 cm) and in the number of leaves of the outbreak of the graft with (9.10); While the (T1) CCN – 51 was higher than the (T1) EET – 575 in the parameters of height of the outbreak of the graft with (19.82 cm) and in the leaf area (96.82). I therefore that the best alternative among the three clones in study of cocoa evaluated, responded with greater significance the (T1) CCN – 51 and the (T2) EET – 575, which expressed genetic characters and physiological favorable toward the kind of vegetative propagation, Under the method of graft plectrum lateral amended type Mummy, in terms of Central Huallaga.